1999
DOI: 10.1046/j.1471-4159.1999.0730605.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 Induction by Tumor Necrosis Factor‐α and Involvement of p53 in Cell Death of Human Oligodendrocytes

Abstract: Oligodendrocytes (OLs) and their myelin mem-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 34 publications
3
49
0
Order By: Relevance
“…In a previous report, we showed that exposure of human adult OLs to the pro-inflammatory cytokine TNFa was associated with the up-regulation and nuclear translocation of the tumor-suppressor gene p53, a major regulator of apoptotic pathways. We also showed that overexpressing p53 in human adult OLs in culture induces rapid apoptosis in these cells (Ladiwala et al 1999).…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…In a previous report, we showed that exposure of human adult OLs to the pro-inflammatory cytokine TNFa was associated with the up-regulation and nuclear translocation of the tumor-suppressor gene p53, a major regulator of apoptotic pathways. We also showed that overexpressing p53 in human adult OLs in culture induces rapid apoptosis in these cells (Ladiwala et al 1999).…”
mentioning
confidence: 70%
“…The protocol was approved by an institutional review board according to the guidelines of the Canadian Institutes for Health Research. OLs were isolated as previously described (D'Souza et al 1996;Ladiwala et al 1999;Pouly et al 2000). Briefly, brain tissue was dissociated enzymatically with trypsin and DNAse, and mechanically by passage through a 132-lm nylon mesh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of TNF-␣ was based on the consideration that these concentrations best mimic a pathological condition similar to the one present in vivo. In addition, the use of this concentration for treatments of oligodendrocyte-derived cell cul-tures and primary oligodendrocytes has been documented by several previous studies (Hisahara et al, 1997;Ladiwala et al, 1999;Ye and D'Ercole, 1999;Cammer, 2000;Buntinx et al, 2004b). The cells were harvested by trypsinization, and the cells that could not be trypsinized were scraped off in cold PBS containing proteinase inhibitor mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Although as a proinflammatory cytokine TNF␣ often opposes p53 activity (62), it has been shown to induce p53 and increase p53-dependent apoptosis (63). Conversely p53 may increase TNF␣-dependent apoptosis through induction of a proapoptotic factor (64) or indirectly regulate TNF␣ signaling through the GR.…”
Section: Discussionmentioning
confidence: 99%